Cultural Shifts as the Identity of Klungkung Village, Jember Regency in the Era of Globalization - Lokaprasidha, Pramesi; Hutama, Pandu Satriya; Ramadhani, Sofina Adwitya; Warda Ayu Berliana Nafis; Indartik, Ninik Wahyu (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2024)
Globalization has brought significant changes to various aspects of life, including economic, social, political, and cultural dimensions. Klungkung Village, located in Jember Regency, has also been impacted by globalization. Advances in technology and the rapid flow of information have brought significant changes to various aspects of life in Klungkung Village. Globalization has accelerated the dissemination of information and cultures from around the world, which then interact and integrate with the local culture. This phenomenon poses a new challenge for the community of Klungkung Village in maintaining and preserving their rich and unique cultural identity. The purpose of this study is to identify and analyze the forms of cultural shifts occurring and to understand their impact on the village's cultural identity. The research methodology uses a qualitative approach with data collection techniques through participatory observation, in-depth interviews, and literature studies. The results of the study show that although there is a shift in cultural practices, the community of Klungkung Village is able to maintain the essence of their cultural identity by adapting and integrating new elements without diminishing the cultural values. This research will make an important contribution to understanding the dynamics of local culture amidst the tide of globalization and offer perspectives on effective cultural preservation strategies in the modern era.